2016
DOI: 10.1517/17425255.2016.1154044
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic, pharmacodynamic and clinical evaluation of saxagliptin in type 2 diabetes

Abstract: Saxagliptin is routinely used in the management of type 2 diabetes as monotherapy, and in combination with other oral agents and insulin. Robust clinical trials have shown consistent improvements in glycated hemoglobin, fasting and postprandial glucose levels, with few adverse effects. The agent is well tolerated with low rates of hypoglycemia in the absence of insulin or sulphonylurea therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…These findings have resulted in eight commercially available DPP-IV inhibitors, including alogliptin (Nesina ® , Vipidia ® ; Keating, 2015;Takeda et al, 2016), anagliptin , gemigliptin (Zemiglo ® ; Kim et al, 2013;Jung et al, 2014), linagliptin (Forst and Pfutzner, 2012;Barnett, 2015), saxagliptin Anderson et al, 2016), sitagliptin (Januvia ® , Xelevia ® , Glactiv ® , Tesavel ® ; Garg et al, 2013;Plosker, 2014), teneligliptin (Nakamaru et al, 2015), and vildagliptin (Galvus ® , Novartis AG; Mikhail, 2008;Richter et al, 2008), being approved and entering into the clinic . These DPP-IV inhibitors have good oral bioavailability and a relatively long duration of action in patients with T2DM.…”
Section: Dpp-iv Inhibitor and T2dmmentioning
confidence: 99%
“…These findings have resulted in eight commercially available DPP-IV inhibitors, including alogliptin (Nesina ® , Vipidia ® ; Keating, 2015;Takeda et al, 2016), anagliptin , gemigliptin (Zemiglo ® ; Kim et al, 2013;Jung et al, 2014), linagliptin (Forst and Pfutzner, 2012;Barnett, 2015), saxagliptin Anderson et al, 2016), sitagliptin (Januvia ® , Xelevia ® , Glactiv ® , Tesavel ® ; Garg et al, 2013;Plosker, 2014), teneligliptin (Nakamaru et al, 2015), and vildagliptin (Galvus ® , Novartis AG; Mikhail, 2008;Richter et al, 2008), being approved and entering into the clinic . These DPP-IV inhibitors have good oral bioavailability and a relatively long duration of action in patients with T2DM.…”
Section: Dpp-iv Inhibitor and T2dmmentioning
confidence: 99%
“…Several reviews comparing saxagliptin and/or other marketed DPP-4 inhibitors are available in the literature [19][20][21][22][23]. This review focuses on the clinical pharmacological characteristics of saxagliptin.…”
Section: Introductionmentioning
confidence: 99%
“…Other DPP-4 inhibitors have shown 2-to 6-fold increases in the plasma GLP-1 levels in patients with T2DM. 17,[24][25][26][27] Thus, the present study showed that fotagliptin can increase active GLP-1 levels in patients with T2DM more efficaciously than other reported DPP-4 inhibitors. This study supports a once-daily treatment of fotagliptin in patients with T2DM.…”
Section: Discussionmentioning
confidence: 78%